Population-Based Imaging and Radiomics: Rationale and Perspective of the German National Cohort MRI Study - Schlett, C. L.; Hendel, T.; Weckbach, S.; Reiser, M.; Kauczor, H. U.; Nikolaou, K.; Günther, M.; Forsting, M.; Hosten, N.; Völzke, H.; Bamberg, F. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
The MRI study within the German National Cohort, a large-scale, population-based, longitudinal study in Germany, comprises comprehensive characterization and phenotyping of a total of 30 000 participants using 3-Tesla whole-body MR imaging. A multi-centric study design was established together with dedicated core facilities for e. g. managing incidental findings or providing quality assurance. As such, the study represents a unique opportunity to substantially impact imaging-based risk stratification leading to personalized and precision medicine. Supported by the developments in the field of computational science, the newly developing scientific field of radiomics has large potential for the future. In the present article we provide an overview on population-based imaging and Radiomics and conceptualize the rationale and design of the MRI study within the German National Cohort.Key Points:• Population-based imaging and Radiomics constitute two emerging fields with great oppertunities and challenges for Radiology.• As part of the MRI-study of the NAKO approximately 30 000 subjects will undergo 3 Tesla whole-body MRI.• MR Imaging data is publicly accessable and will provide important insights into the natural history of disease processes and personalized risk profiles of the general population. Citation Format:• Schlett CL, Hendel T, Weckbach S et al. Population-Based Imaging and Radiomics: Rationale and Perspective of the German National Cohort MRI Study. Fortschr Röntgenstr 2016; 188: 652 – 661
Keywords: German National Cohort; population-based imaging; longitudinal cohort study; whole-body magnetic resonance imaging; phenotyping; radiomics